4-H Entomology Project, Advanced Level: Working with Insects - Philip G. Koehler; J. C. Northrop (EDIS)
This document is 4HENM12 of the Florida 4-H Youth Development Program, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Reviewed June 2002.